Mulla Sadra and Descartes on the Meaning, the Quiddity and the Ontology of Intellect - Sayed Mahdi Emami Jomie; Mina Mehdizadeh (حکمت اسرا)
Mulla Sadra mentioned some meanings for intellect which some of them refer to practical wisdom and others to theoretical. Mulla Sadra believes that intellect is continuous reality in man who is capable of becoming incorporeal essence by Substantial Motion under the shadow of Active Intellect. Descartes believes that reason distinguishing right from wrong makes a distinction between man and other creatures and has the potentiality of right judgment. In his opinion, this is a similar faculty in all human beings. The meaning of reason in Descartes should be found by its function in philosophy that derives from Mathematics. Reason and method are different just conceptually. Reason in Descartes is the same level of Habitual Intellect (Aql bi al-Malaka) in Mulla Sadra's Philosophy but it is not enough for Mulla Sadra; so he expands it and considers some levels for it. Both philosophers meant reasoning under the shadow of intellect and intuition. Mulla Sadra believes that human's intellect can reach to ontological end to see Separated Intellects and to receive intellectual Forms but Descartes believes that the light of reasoning is the same innate reason that understands things clearly and distinctly.